Phage-induced disturbance of a marine sponge microbiome - Steiner, LX; Schmittmann, L; Rahn, T; Lachnit, T; Jahn, MT; Hentschel, U (BioMed Central, 2024)
Background: Bacteriophages are known modulators of community composition and activity in environmental and host-associated microbiomes. However, the impact single phages have on bacterial community dynamics under viral predation, the extent and duration of their effect, are not completely understood. In this study, we combine morphological and genomic characterization of a novel marine phage, isolated from the Baltic sponge Halichondria panicea, and report on first attempts of controlled phage-manipulation of natural sponge-associated microbiomes. Results: We used culture-based and culture-independent (16S rRNA gene amplicon sequencing) methods to investigate bacterial community composition and dynamics in sponge microbiomes with and without the addition of phages. Upon application of a novel Maribacter specialist phage Panino under controlled conditions, we were able to detect community-wide shifts in the microbiome composition and load after 72 h. While bacterial community composition became more dissimilar over time in the presence of phages, species evenness and richness were maintained. Upon phage exposure, we observed the loss of several low-abundance constituent taxa of the resident microbiota, while other originally underrepresented taxa increased. Virulent phages likely induce community-wide disturbances, evident in changes in the total sponge microbial profile by specific elimination of constituent taxa, which leads to an increase in bacterial abundance of opportunistic taxa, such as the genera Vibrio, Pseudoalteromonas, and Photobacterium. Conclusions: Our findings suggest that sponge microbiome diversity and, by extension, its resilience depend on the maintenance of resident bacterial community members, irrespective of their abundance. Phage-induced disturbances can significantly alter community structure by promoting the growth of opportunistic bacteria like Vibrio and shifting the microbiome to a dysbiotic state. These insights highlight the role of bacteriophages in shaping microbiome dynamics and underscore the potential for phage application in managing bacterial community composition in marine host-associated environments.